Phage resistance formation and fitness costs of hypervirulent Klebsiella pneumoniae mediated by K2 capsule-specific phage and the corresponding mechanisms - Tang, Miran; Huang, Zeyu; Zhang, Xiaodong; Kong, Jingchun; Zhou, Beibei; Han, Yijia; Zhang, Yi; Chen, Lijiang; Zhou, Tieli (Frontiers in Microbiology, 2023)
Introduction Phage is promising for the treatment of hypervirulent Klebsiella pneumoniae (hvKP) infections. Although phage resistance seems inevitable, we found that there still was optimization space in phage therapy for hvKP infection. Methods The clinical isolate K. pneumoniae FK1979 was used to recover the lysis phage ΦFK1979 from hospital sewage. Phage-resistant bacteria were obtained on LB agar and used to isolate phages from sewage. The plaque assay, transmission electron microscopy (TEM), multiplicity of infection test, one-step growth curve assay, and genome analysis were performed to characterize the phages. Colony morphology, precipitation test and scanning electron microscope were used to characterize the bacteria. The absorption test, spot test and efficiency of plating (EOP) assay were used to identify the sensitivity of bacteria to phages. Whole genome sequencing (WGS) was used to identify gene mutations of phage-resistant bacteria. The gene expression levels were detected by RT-qPCR. Genes knockout and complementation of the mutant genes were performed. The change of capsules was detected by capsule quantification and TEM. The growth kinetics, serum resistance, biofilm formation, adhesion and invasion to A549 and RAW 264.7 cells, as well as G. mellonella and mice infection models, were used to evaluate the fitness and virulence of bacteria. Results and discussion Here, we demonstrated that K2 capsule type sequence type 86 hvKP FK1979, one of the main pandemic lineages of hvKP with thick capsule, rapidly developed resistance to a K2-specific lysis phage ΦFK1979 which was well-studied in this work to possess polysaccharide depolymerase. The phage-resistant mutants showed a marked decrease in capsule expression. WGS revealed single nucleotide polymorphism (SNP) in genes encoding RfaH, galU, sugar glycosyltransferase, and polysaccharide deacetylase family protein in the mutants. RfaH and galU were further identified as being required for capsule production and phage sensitivity. Expressions of genes involved in the biosynthesis or regulation of capsule and/or lipopolysaccharide significantly decreased in the mutants. Despite the rapid and frequent development of phage resistance being a disadvantage, the attenuation of virulence and fitness in vitro and in vivo indicated that phage-resistant mutants of hvKP were more susceptible to the immunity system. Interestingly, the newly isolated phages targeting mutants changed significantly in their plaque and virus particle morphology. Their genomes were much larger than and significantly different from that of ΦFK1979. They possessed much more functional proteins and strikingly broader host spectrums than ΦFK1979. Our study suggests that K2-specific phage has the potential to function as an antivirulence agent, or a part of phage cocktails combined with phages targeting phage-resistant bacteria, against hvKP-relevant infections.